Identification of key miRNAs affecting broilers with valgus–varus deformity by RNA sequencing and analysis of miRNA–mRNA interactions. (24th June 2021) - Zhang, Zhenzhen; Tang, Hehe; Ma, Yanchao; Li, Jianzeng; Li, Zhuanjian; Zhang, Yanhua; Li, Yuanfang; Kang, Xiangtao; Han, Ruili
Abstract : 50 differentially expressed miRNAs were screened by RNA sequencing of broilers with Valgus–varus Deformity, GO and KEGG pathway analyses were performed. DE mRNAs were combined and the mRNA–miRNA networks were drawn. Abstract : Valgus–varus Deformity (VVD) leg disease often affects chickens raised in modern large-scale breeding operations. Losses due to VVD are costly to farmers, and the condition also causes significant suffering in affected birds. In this study, we profiled RNAs from the spleens of VVD (BS) and healthy (JS) broilers using high-throughput sequencing to identify miRNAs that might be involved in the development of the disease. Fifty differentially expressed miRNAs (DEMs) were found, of which 30 were up-regulated and 20 were down-regulated in VVD-affected birds (|log 2 Fold Change| ≥ 1 and q -value < 0.05). DEMs were matched with putative target genes and 864 target genes were found. Gene Ontology (GO) analyses of these target genes showed that they were significantly enriched in the "cytoplasm" term ( q -value < 0.05), and most of the target genes were enriched in "cellular component". Kyoto encyclopedia of genes and genomes (KEGG) analysis showed that they were significantly enriched in 11 signaling pathways ( P -value < 0.05), including metabolic pathways, 2-oxocarboxylic acid metabolism, regulation of actin cytoskeleton, purine metabolism, endocytosis and so on. And we found that they were enriched in immune-related pathways in which MAPK, Notch, JAK-Stat, Toll-like receptor, p53 and other single pathways were involved in the development of skeletal diseases. Differentially expressed mRNAs obtained from our previous study were used to construct an interaction network consisting of 16 DEMs and 21 differentially expressed mRNAs (|log 2 Fold Change| ≥ 1 and q -value < 0.05). We found that miR-12247-5p, miR-15c-5p, miR-15b-5p, FKBP5 and HSP90AB1 were at the center of network interaction. This study provides a foundation for further investigations of the pathogenesis and genetic mechanisms underlying VVD.